pyroelectric and dielectric properties of single triglycine sulphate crystal under different poling temperatures - Fatma A. E. Almashay; Alhakimah A. H. Aleshi (African Journal of Advanced Pure and Applied Sciences, 2026)
In the present work, dielectric constant measurements in the vicinity of the phase transition point (Tc) ≈49⁰C and so pyroelectric current measurements after poling process at different temperatures and constant poling field of 4kv/cm subjected on samples of triglycine sulphate were cut from a large single crystal. The results show that the maximum value of the dielectric constant at the transition temperature (Tc) decreases with increasing the frequency and that the peak shifts to lower temperatures and it was found that by increasing the poling temperature the peak of pyroelectric current increases and shifts to lower temperatures.